2022
DOI: 10.1155/2022/8482415
|View full text |Cite
|
Sign up to set email alerts
|

A Data Management Model for Intelligent Water Project Construction Based on Blockchain

Abstract: The engineering construction-related data is essential for evaluating and tracing project quality in industry 4.0. Specifically, the preservation of the information is of great significance to the safety of intelligent water projects. This paper proposes a blockchain-based data management model for intelligent water projects to achieve standardization management and long-term preservation of archives. Based on studying the concrete production process in water conservancy project construction, we first build a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Utilization of data management and integration during construction (e.g., stakeholder and supervision team to update data in real-time, and document traceability such as storing material testing, products, and document approvals) [101,132,133] Table A2. Cont.…”
Section: C01 Technologymentioning
confidence: 99%
“…Utilization of data management and integration during construction (e.g., stakeholder and supervision team to update data in real-time, and document traceability such as storing material testing, products, and document approvals) [101,132,133] Table A2. Cont.…”
Section: C01 Technologymentioning
confidence: 99%
“…Many of them emphasize the benefits of blockchain with live data [23], provide a platform for running AI predictions on real-time data, and use blockchain to incentivize accurate forecasts. Wang et al [24] demonstrate the ability of blockchain to track and record data to achieve long-term preservation of records. They developed a behavioral model, followed by the development of a distributed blockchain data structure for storing output documents directly in line with the approaches and strategies.…”
Section: Blockchain Capabilities To Track and Record Datamentioning
confidence: 99%
“…Furthermore, data were uploaded onto the blockchain to efficiently control quality and safety of intelligent water project construction. Experiments revealed that the proposed strategy decreased time and labor costs while creating production data and ensuring the security and traceability of electronic document preservation [24].…”
Section: Blockchain Capabilities To Track and Record Datamentioning
confidence: 99%